Invasive Beatmungstherapie im Sterbeprozess beenden – Schritt für Schritt - Schwartz, Jacqueline; Meier, Stefan; Simon, Steffen T.; Michels, Guido (DMW - Deutsche Medizinische Wochenschrift, 2020)
Invasive mechanical ventilation can be terminated by immediate (palliative) extubation or by gradual reduction of ventilation with the ventilation access left open (terminal weaning). Both procedures are ethically equivalent and can be performed in everyday life, so that individual patient factors and the experience of the treatment team are decisive. However, the primary goal is to ensure that the patient and relatives do not suffer. This article presents step by step which aspects are relevant: communication, adjust or stop monitoring, selection and implementation of the appropriate procedure, preparatory measures, recognition and treatment of distressing symptoms by means of drug or non-drug therapy options and last but not least accurate documentation.
Keywords: palliative Extubation; terminales Weaning; Palliative Care; Management am Lebensende; Intensivmedizin